2007
DOI: 10.1117/1.2795688
|View full text |Cite
|
Sign up to set email alerts
|

Detection and treatment of dysplasia in Barrett’s esophagus: a pivotal challenge in translating biophotonics from bench to bedside

Abstract: Barrett's esophagus (BE) is a condition that poses high risk of developing dysplasia leading to cancer. Detection of dysplasia is a critical element in determining therapy but is extremely challenging, so that standard white-light endoscopy is used only as a means to guide biopsy. Many novel optical techniques have been aimed at this problem, including various forms of improved wide-field white-light (chromoendscopy/magnification and narrow-band) and fluorescence imaging, and "optical biopsy" techniques (diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 90 publications
0
53
0
Order By: Relevance
“…A number of advanced techniques have demonstrated potential as promising clinical tools in assisting physicians with timely and accurate diagnosis. [6][7][8] Light-scattering spectroscopy (LSS), 9 for instance, obtains quantitative information of nuclear morphology by extracting the singly backscattered light from epithelial layers of tissue using modeling. LSS has been shown effective for in vivo identification of precancerous cells in a variety of epithelial tissues using the population density and percentage of enlarged cell nuclei as biomarkers; [10][11][12] although, certain aspects of the approach have recently been called into question.…”
Section: Introductionmentioning
confidence: 99%
“…A number of advanced techniques have demonstrated potential as promising clinical tools in assisting physicians with timely and accurate diagnosis. [6][7][8] Light-scattering spectroscopy (LSS), 9 for instance, obtains quantitative information of nuclear morphology by extracting the singly backscattered light from epithelial layers of tissue using modeling. LSS has been shown effective for in vivo identification of precancerous cells in a variety of epithelial tissues using the population density and percentage of enlarged cell nuclei as biomarkers; [10][11][12] although, certain aspects of the approach have recently been called into question.…”
Section: Introductionmentioning
confidence: 99%
“…Given the background squared scattering amplitude (6) and (8) specified, respectively, in the fractal and Whittle-Matern models, the scattering properties originating from the background refractive fluctuation is simply determined by Eqs. (2)(3)(4). Figure 1 shows the trends of various scattering properties: the scattering coefficient μ s , the reduced scattering coefficient μ s , the anisotropy factor g ≡ 1 − μ s /μ s , and the scattering power b (μ s ∝ λ −b ) predicted by the two models.…”
Section: Background Refractive Index Fluctuationmentioning
confidence: 99%
“…(3,4). For most tissues, the size parameter of their core within visible and near-infrared spectral range is less than 1.245 |m c − 1| −1.725 and resides in the neighborhood of 2 |m c − 1| −1 .…”
Section: Plum Pudding Random Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Numerous endoscopic applications for tracking exogenous targeted fluorescence are under investigation, such as detection and diagnosis of early cancerous lesions in Barrett's esophagus, 7 navigation and demarcation of tumor margins during brain surgery, 8,9 and detection of early neoplasia in oral tissue, 10 lung, 11 bladder, 12 and smaller gastrointestinal (GI) ducts. 13 Moreover, translational studies for first-in-human application of fluorescence molecular targets have been demonstrated in colonic dysplasia detection as well as surgical guidance for ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%